Science Teaching through experimentation: building a yeast volcano (Research, Society and Development, 2020)
This investigation aims to lead students to think, debate, justify their ideas when studying the chemical processes of fermentation and catalase action, through of experimentation, in a State Public School located in the city of Santa Maria/RS. The work was developed in the laboratory of the school with a 6th grade class, during science classes and had the collaboration of the responsible teacher. The data were obtained through the application of a pre-test questionnaire with four open questions; in addition to a post-test through an open question regarding the understanding of the yeast volcano experiment. The results of the pre-test questionnaire demonstrated the need to amplify classroom discussions about basic science teaching processes based on everyday life, due the low discernment capacity of students. In contrast, during the experiment the students were curious and interested in understanding the processes that occurred in the yeast volcano. Thus, it can be seen that students learn more when exposed to different situations and the importance of experimentation in the teaching and learning process stands out, facilitating the discussion between them.